Keeping Choro Alive in Brazilian Concert Music for Bassoon - Pedrosa, Ariana (Revue musicale OICRM, 2019)
Brazilian concert music for bassoon—the fruit of the Brazilian nationalist movement of the 19th and 20th centuries—is challenging for performers due to the circumstances in which this repertoire emerged and the influences underlying it. Here, the role of Brazilian popular music in the formation and establishment of this repertoire is often unstated or understated. One important popular genre unique to Brazil is choro. It is impossible to deliver a faithful performance of many of the Brazilian nationalist music pieces heavily influenced by choro without some acquaintance with this genre. These considerations have become especially relevant due to the widespread popularity of Brazilian concert music repertoire for bassoon all around the world. Informed performance practice in ‘good taste’ can result, among other, from closing the gaps in knowledge, providing sufficient and clear background and reference information, raising awareness for practices and conventions of the time and style, and passing on the insight of those close to the source in a manner of oral tradition.